2018
DOI: 10.1194/jlr.p082834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mipomersen, an apolipoprotein B100 antisense, on lipoprotein (a) metabolism in healthy subjects

Abstract: Effects of mipomersen, an apolipoprotein B100 antisense, on lipoprotein (a) metabolism in healthy subjects. J LipidRes. 2018. 59: 2397-2402.Supplementary key words fractional clearance rate • production rate • apoB antisense treatment Lipoprotein (a) [Lp(a)] is a lipoprotein particle similar in lipid and protein composition to LDL. It is present in plasma mainly in the density range of 1.019 to 1.120 g/ml and has recently been described as a carrier of proinflammatory oxidized phospholipids (1). The hallmark o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Interventional studies on plasma Lp(a) levels with different lipid-lowering drugs exhibiting various mechanisms of action (PCSK9 inhibitor, 18 apoB100 antisense oligonucleotide, 45 CETP inhibitor, 46,47 ezetimibe, 48 fibrates, 48,49 and statins 37,[49][50][51] ) also suggested that plasma Lp(a) reduction is associated with a decrease in the total or VLDL apoE concentration. A decrease in the Lp(a) production rate is the most frequently offered explanation for Lp(a) reduction, irrespective of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Interventional studies on plasma Lp(a) levels with different lipid-lowering drugs exhibiting various mechanisms of action (PCSK9 inhibitor, 18 apoB100 antisense oligonucleotide, 45 CETP inhibitor, 46,47 ezetimibe, 48 fibrates, 48,49 and statins 37,[49][50][51] ) also suggested that plasma Lp(a) reduction is associated with a decrease in the total or VLDL apoE concentration. A decrease in the Lp(a) production rate is the most frequently offered explanation for Lp(a) reduction, irrespective of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In statin-treated patients, the fractional turnovers of apo(a) and apoB proteins within Lp(a) are similar, thus reflecting a tight coupling of these protein components. A recent kinetic study relative to the production rate of Lp(a) suggested that the hepatic availability of apoB is unlikely to be rate-limiting for the assembly and production of Lp(a) particles [ 54 ]. Overall, the molecular mechanisms responsible for Lp(a) catabolism still remain elusive, with several receptor systems being proposed as implicated in this process (lipoprotein receptors, toll-like and scavenger receptors, lectins, and plasminogen receptors) [ 55 ].…”
Section: Statinsmentioning
confidence: 99%
“…The mechanism underlying this effect was recently the subject of a comprehensive investigation. Another option could be mipomersen, an apoB inhibitor, which could correlate with the reduction of Lp(a) ∼30% 57) ; however, it almost always causes fatty liver since it blocks the secretion of apoB-containing lipoproteins from the liver. Another emerging option could be antisense oligonucleotide (ASO) targeted to apolipoprotein(a).…”
Section: Lp(a)-lowering Therapiesmentioning
confidence: 99%